CUSTOMER LOYALTY AND BRAND FAILURE: AN IMPERATIVE CASE OF FAST FOOD INDUSTRY IN THE WEST AFRICA AFRICAN REGION (Singaporean Journal of Business Economics and Management, 2015)
Over the past decades, developed countries have had significant input from the fast food industry on the national Gross Domestic Product (GDP) but to the developing countries, this has really been a nightmare. Since majority of the fast food restaurants wounds up few years after setup and are bewildered by short product life cycle. At such a teaming percentage of the country’s population looses their jobs and these have really discouraged young entrepreneurs and foreign investor from investing in this promising industry in the West African States. This study examines the relationship between service quality, customer satisfaction, customer loyalty, examined factors that prompt repeat purchase and brand failure in the fast food industry in the West African Region. The study adopted a sample size of 820 consumers from different fast food restaurant which was taken randomly on the basis of convenience sampling across 8 West African Countries which include; Benin, Gambia, Ghana, Guinea, Liberia, Nigeria, Senegal and Sierra Leone. Multiple Regressions were used as the statistical tool. Results obtained from the analysis corroborate that there is a significant impact of service quality on the customer loyalty and brand failure on customer satisfaction. This study showcased how to gain customer loyalty towards a particular brand and the factors that leads to product failure and also made recommendations and suggestions for areas for further studies.